Education in New France - Magnuson, Roger (McGill-Queen's University Press, 1992)
"The first priority of French missionaries in New France was the conversion of the native population. Education was an important tool in the evangelization campaign because they believed that conversion was best secured when preceded and underscored by religious instruction. As Canada evolved into a French colony the religious orders increasingly turned their attention to the education of the children of French settlers. The period saw the establishment of a number of petites ecoles (elementary schools), a Jesuit college for boys, and several trade schools." "Roger Magnuson demonstrates that provision for education in the colony declined during the eighteenth century. First, membership in religious orders dwindled, reducing their capacity to serve the educational needs of an expanding population. Second, as the population of the colony grew, with more inhabitants born in Canada than in France, different values and priorities developed. The written word, notes Magnuson, held less attraction for the Canadian, who preferred the active life of the frontier."--Jacket